ANALISIS KADAR ASAM LAKTAT DENGAN INTENSITAS LOW BACK PAIN PADA PEMANEN SAWIT PT X KABUPATEN KAMPAR - yuharika pratiwi; Hengky Ardian; Nova Melinda (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
Background: Repetitive movements and poor body posture during work often cause low back pain (LBP), which radiates pain from the corner of the lowest ribs to the corner of the buttocks in the lumbar-sacral area. The prevalence of LBP ranges between 60 - 80% in the world. Risk factors for LBP in workers are excessive workload on the bones, which causes injury or trauma to soft tissue. Palm harvesters often experience muscle tension due to awkward postures for long periods, resulting in increased lactic acid levels, which are related to the intensity of LBP. An initial survey of PT Objective: To determine the analysis of the relationship between lactic acid levels and low back pain in palm oil harvesters at PT. X Kampar Regency Method: This research is an observational analytic, cross-sectional design. The sampling technique uses total sampling, with statistical tests using the Spearman test. Results: The results of the Spearman correlation test showed that p-value = 0.000; r 0.649 with a strong positive relationship strength. Conclusion: There is a relationship between lactic acid levels and LBP intensity in PT palm oil harvesters. X.